2018 1st International Conference on Computer Applications &Amp; Information Security (ICCAIS) 2018
DOI: 10.1109/cais.2018.8441952
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Detection Method to Mitigate DoS Attacks in MANETs

Abstract: A Mobile ad hoc Network (MANET) is a selfconfigure, dynamic, and non-fixed infrastructure that consists of many nodes. These nodes communicate with each other without an administrative point. However, due to its nature MANET becomes prone to many attacks such as DoS attacks. DoS attack is a severe as it prevents legitimate users from accessing to their authorised services. Monitoring, Detection, and rehabilitation (MrDR) method is proposed to detect DoS attacks. MrDR method is based on calculating different tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Therefore, a malicious and fake route will be created. When this route has been set up, now it is depending on the node whether to drop the packet or to forward them to an unknown (Alsumayt et al, 2018).…”
Section: Black Hole Attackmentioning
confidence: 99%
“…Therefore, a malicious and fake route will be created. When this route has been set up, now it is depending on the node whether to drop the packet or to forward them to an unknown (Alsumayt et al, 2018).…”
Section: Black Hole Attackmentioning
confidence: 99%
“…Also, it has been observed that the detection rate has not been affected by the node movement and network's size. Alsumayt et al [9] presented a new technique named "monitoring detection and rehabilitation" to prevent the network from DoS attack. This technique is based on measuring the number of actual values that the sensor node can be trustworthy or not.…”
Section: Related Workmentioning
confidence: 99%
“…Other methods use a trust concept between nodes in MANETs that need IP address configuration in the event of MANET merging. Both traditional and other methods used to detect DoS attacks based on trust concepts are discussed in detail in (Alsumayt and Haggerty, 2014a); (Alsumayt and Haggerty, 2014b). The current section briefly presents a summary of studies that aim to configure IP addresses in the merging scenario and the methods used for misbehaviour detection.…”
Section: Related Workmentioning
confidence: 99%